« Il n’est pas mort. Il vit encore ! »Analyse anthropologique des systèmes relationnels dans le don d’organes - Luigigiovanni Quarta (Anthropologie & Santé)
Based on ethnographic fieldwork about organ donation in Italy, the article addresses some of the problems at the heart of the moral construction of identity and personhood in the contemporary world. The aim is to discuss the experience of the transformation of death into a factor in the production of life. This essential element in the reconstruction of selfhood is generated at the intersection of models of practices and temporalities. It differs according to the perspective from which the individual subjects involved consider the world around them. What remains at the end of this investigation is an open-ended and ever-renewable question: how does our ability to define what is properly human change with respect to medical and technological breakthroughs?